Functions, responsibility and authority of human resources in the implementation of a security and safety management system at work. (2012)
ABSTRACT: A security and safety management system at work must fulfill a number of general and particular requirements that allow to promote good practices in order to achieve the objectives of the policy approved by the organization. Risk assessment and control is not an easy task; it requires significant material and human resources. In the implementation and operation of a management system the human resources devoted exclusively to security and safety at work play an essential role. It is necessary to establish the organization chart of these resources and to define the functions and responsibilities of each of the areas composing the Security and Safety Service of the company that are not detailed in the known standards. In this work, based on the knowledge of preventive techniques, the structure of a complex prevention service is described. This structure can be used as a practical model.